In Vitro Evaluation of Nanochitosan Derivatives and Streptomycin on RD Cell Line and Leishmania Tropica - Ahmed, Ali Shehab; Khayri, Muna Mohammed; Al-Halbosiy, Mohammed M. F (Al-Nahrain Journal of Science, 2017)
The study aimed to evaluate in vitro the efficiency of the nano-encapsulated streptomycin within carboxymethylnanochitosan synthesized by an acid-base method on Rhabdomyosarcoma RD cell line and Leishmania tropica. Results showed that the concentrations 100 and 50 µg/ml of encapsulated streptomycin were more effective than 50 and 100 µg/ml of streptomycin alone and inhibited the growth of RD cells to 56 and 35 vs. 19.45 and 23% respectively after 24 hrs of incubation. Carboxymethylnanochitosan at a concentration of 50 µg/ml has the anticancer ability since it inhibited the growth of RD cells up to 20% in comparison with 19% for streptomycin at the same concentration. The growth inhibition of L. tropica in the presence of streptomycin, carboxymethylnanochitosan and streptomycin encapsulated within carboxymethylnanochitosan at 100 µg/ml for each was 34.4, 36 and 29.5% respectively. Carboxymethylnanochitosan is then considered the most effective inhibitor of L. tropica growth.